EFFECTS OF USNIC ACID ON THE OXYGEN-EXCHANGE PROPERTIES OF MESOPHYLL CELL PROTOPLASTS FROM COMMELINA-COMMUNIS L - VAVASSEUR, A; GAUTIER, H; THIBAUD, M C; LASCEVE, G (JOURNAL OF PLANT PHYSIOLOGY, 1991)
Usnic acid, a phenolic compound synthesised by Usnea sp. totally inhibits oxygen evolution of illuminated mesophyll cell protoplasts from Commelina communis L. at a concentration of 4-mu-M. This inhibition was not reversed by manganese ions, as previously observed with chloroplasts extracted from leaves of Quercus rotundifolia treated with usnic acid. At 10-mu-M usnic acid, dark respiration was 59% inhibited within 10 min and eliminated after 200 min. Usnic acid rapidly affects the oxidative phosphorylation pathway and later the alternative oxidase pathway. The different responses of isolated chloroplasts, protoplasts and whole plant to usnic acid are discussed.
Keywords: COMMELINA-COMMUNIS L; LICHENIC ACIDS; MESOPHYLL PROTOPLAST